Identification and Antibacterial Activity of Bioactive Compounds Extracted from Gading Coconut (Cocos nucifera var. eburnea) Leaf - Hasanah, Uswatun; Mulyati, Ade Heri; Riyadi, Sandra Amalia; Pita, Lusia Magdalenis (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2025)
Traditional medicine continues to play a vital role in Indonesia’s healthcare landscape, with increasing reliance on plant-derived remedies for disease prevention and treatment. Among these, the gading coconut (Cocos nucifera var. eburnea), native to Bogor, Indonesia, presents untapped potential as a source of antibacterial agents. This study aimed to identify bioactive compounds with antibacterial activity from gading coconut leaves and to evaluate the impact of extraction methods—maceration and sonication—on their yield and efficacy. Compared with maceration (5.92%), sonication produced a significantly greater extract yield (9.48%). Phytochemical screening confirmed the presence of alkaloids, flavonoids, and tannins in both extracts. Quantitative analysis revealed that the sonicated extract contained greater concentrations of total flavonoids (52.06 mg QE/g) and total phenolics (147.10 mg GAE/g). Chemical profiling using liquid chromatography‒tandem mass spectrometry (LC‒MS/MS) identified key antibacterial constituents, including 3-hydroxycoumarin, isoorientin, vitexin, and α-linolenic acid. Biological evaluation demonstrated that the sonicated extract exhibited stronger antibacterial activity, with minimum inhibitory concentrations (MICs) of 50 mg/mL against Escherichia coli and 25 mg/mL against Staphylococcus aureus. These findings suggest that the extraction method significantly influences both the chemical composition and antibacterial potency of gading coconut leaf extracts. Overall, this study highlights the pharmacological relevance of C. nucifera var. eburnea as a promising source of natural antibacterial agents and contributes to the scientific validation of traditional medicinal plants in Indonesia.